Systemic cell-mediated reactions in vivo. Effect of the interaction of circulating antigen with sensitized lymphocytes on glomeruli and pulmonary alveoli. - Bhan, A. K. (1984)
The effects of systemic cell-mediated hypersensitivity reactions on glomeruli and lungs were investigated in rats. The animals were given an intravenous injection of antigen 7 days after sensitization or were given an intravenous injection of lymph node cells from sensitized syngeneic donors 1 day after antigen injection. Control animals were given an irrelevant antigen or saline. All animals received three injections of 3H-thymidine during the course of the experiments. The animals were sacrificed 2 or 3 days after antigen injection. Autoradiographs of renal and pulmonary tissue showed significantly more labeled mononuclear cells in glomeruli and pulmonary alveolar walls in the experimental groups than in the control groups. Immunofluorescence studies did not reveal antigen, rat IgG, or C3 in glomeruli. The results indicate that systemic cell-mediated reactions can lead to an accumulation of mononuclear cells in glomeruli and lungs, an effect that may contribute to tissue injury.